2019
DOI: 10.1088/1741-4326/ab04c0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plasma shape and neutral beam mix on the rotation threshold for RMP-ELM suppression

Abstract: Varying the neutral beam injection (NBI) mix reveals a clear pedestal-top rotation threshold for edge localized mode (ELM) suppression by resonant magnetic perturbations. Guided by expectations for the RMP penetration mechanism, the rotation threshold is found to correspond to a critical radius for the ExB rotation zero-crossing. No such critical radius is observed for the electron perpendicular rotation zero-crossing. Varying the amount and ratio of power in different NBI source geometries (termed the NBI mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 57 publications
13
70
1
Order By: Relevance
“…The threshold exceeds the available RMP amplitude for n e,ped >2.5×10 19 m -3 (black dashed line Fig. 5d), consistent with the ubiquitous density threshold for ELM suppression in DIII-D. 14,15 The three high density discharges with B r /B r,th < 1 are not ELM suppressed and have no observable field penetration event at the pedestal top. The increasing penetration threshold δB r,th /B T with increasing density is due to the increasing inertia of the plasma when the flow frequency is constant, requiring higher RMP levels that eventually exceed the experimentally available RMP amplitude for penetration.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The threshold exceeds the available RMP amplitude for n e,ped >2.5×10 19 m -3 (black dashed line Fig. 5d), consistent with the ubiquitous density threshold for ELM suppression in DIII-D. 14,15 The three high density discharges with B r /B r,th < 1 are not ELM suppressed and have no observable field penetration event at the pedestal top. The increasing penetration threshold δB r,th /B T with increasing density is due to the increasing inertia of the plasma when the flow frequency is constant, requiring higher RMP levels that eventually exceed the experimentally available RMP amplitude for penetration.…”
supporting
confidence: 64%
“…One characteristic of ELM suppression in DIII-D low collisionality (ν * e <0.5) ITER-similar-shape (ISS) plasmas is the low pedestal density n e,ped ≈ 2-3×10 19 m -3 required for access to ELM suppression. 14,15 This requirement at low collisionality raises the question whether ELM suppression can be achieved for the much higher densities expected in ITER. A further characteristic of ISS plasmas is that RMPs can produce a strong density reduction (called pump-out) 6,16 that rapidly diminishes as the density increases.…”
mentioning
confidence: 99%
“…It turns out that, for the case illustrated in Figure 3, −n ω E and the nonlinear natural phase velocity, 0 , take very similar values when −q 95 4.55. Hence, the observations reported in [17] are more consistent with the nonlinear mode penetration model presented in this paper than mode penetration models that employ linear layer physics (which, inevitably, conclude that mode penetration is correlated with ⊥ e passing through zero). Figure 4 illustrates what happens to the calculation shown in Figure 3 if we take the experimental resistivity profile and scale it up by a constant factor.…”
Section: Edge Safety-factor Scansupporting
confidence: 83%
“…The application of a static RMP, resonant in the pedestal region, to an H-mode tokamak discharge is observed to give rise to two distinct phenomena [13,14,15,16,17]. The first of these is the so-called density pump-out, which is characterized by a reduction in the electron number density in the pedestal region that varies smoothly with the amplitude of the applied RMP, is accompanied by a similar, but significantly smaller, reduction in the electron and ion temperatures, but is not associated with ELM suppression.…”
Section: Observed Features Of Rmp-generated Elm Suppressionmentioning
confidence: 99%
“…However, the production of such a well-localized island places stringent constraints on the flow profiles of the plasma that would produce very strict access conditions. Recent work has shown that such flow profiles are not a necessary constraint for ELM suppression 74,79 . These studies suggest that 3D plasma distortions may lead to turbulent transport effects playing a role.…”
Section: Box 2 | Ballooning Modes and Kink Modesmentioning
confidence: 99%